Little Miss Late - Hargreaves, Roger (World international Limited, 1981)
Little Miss Late is the 11th book in the Little Miss series. Little Miss Late is late for everything, and can't find a job. She tries to work in a bank, but by the time she gets there the bank has closed.
Keywords: Juvenile Fiction-Book